Clinical laboratory management - Lynne S. Garcia
Provides thorough coverage of management topics such as managerial leadership, personnel, business planning, information management, regulatory management, reimbursement, generation of revenue, and more. Includes valuable administrative resources, including checklists, worksheets, forms, and online resources